Trigger warning : short fictions and disturbances - Gaiman, Neil (William Morrow, an imprint of HarperCollins Publishers, 2015)
This third collection of short fiction by Gaiman includes previously published pieces of short fiction -- stories, verse, and a very special Doctor Who story that was written for the fiftieth anniversary of the beloved series in 2013 -- as well "Black Dog," a new tale that revisits the world of American Gods.